Remaking the smart city through the COVID-19 pandemic: Seoul, Singapore, Taipei - Woods, Orlando; Chang, I-Chun Catherine; Shin, HaeRan (Applied geography (Sevenoaks), 2025)
The COVID-19 pandemic has proven to be a catalysing force for urban innovation in general, and for smart city agendas specifically, throughout the world. From the development of contact tracing technologies and the enforcement of quarantine and safe distancing measures, to the dissemination of public health information and advancement of telehealth rollouts, the promises of “smart” technologies to reveal and govern patterns of socio-spatial contact and mobility can be found at the core of effective city management during the pandemic. Arguably nowhere is this truer than in the cities of Seoul, Singapore and Taipei, where the Asian developmental state was granted a hitherto unprecedented degree of legitimacy to expand its functions. Drawing on a three-year comparative research project exploring smart city development in Seoul, Singapore, and Taipei and beyond, we explore how the COVID-19 pandemic catalysed urban innovation and reified the importance of smart city projects for effective urban management during public health crises. At the same time, we argue that the catalysing effects of the pandemic led to the creation and extension of “hyper-smartness” throughout the micro-geographies of everyday life, overreach by the state in response to the opportunities for unchecked urban innovation, and the forging of new society-state relations in response. Evidence suggests that recognition of the successes of, and backlash against, technology-enabled urban management has since contributed to the remaking of the smart city in/and the Asian developmental state in the post-pandemic era. •Smart technologies enabled city leaders to better respond to the COVID-19 pandemic.•The Asian development state was given an unprecedented degree of legitimacy to expand its functions.•This led to the creation and extension of “hyper-smartness”, state overreach, and the forging of new society-state relations.•The smart city in/and the Asian developmental state has been remade in the post-pandemic era.